Exploring the Potential of the Land Readjustment Approach in Allocating Land for Affordable Housing from the Market Legitimacy Perspective - Shrestha, Reshma. (2020)
Land Readjustment (LR) is the land development tool applicable in a wide range of application. However, its application in allocating land for low-income housing seems less practiced. Therefore, this study seeks to explore the potential of LR process in accommodating the lowincome groups by allocating low cost land to build low-income housing. To fulfill the objective of this study, two cases were studied. The first case is studied as an exploratory case while second case is studied as explanatory. The results of the cases indicate market legitimacy is the prime factor that drives the land allocation for low cost housing. Besides, to develop inclusive LR there is the need for a policy that takes consideration of market aspect. Furthermore, technical as well as social aspects are important to be considered in the LR process in order to accommodate low-income groups.